2021
DOI: 10.1007/s11606-021-07023-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Personalized Messages Sent by a Health System’s Patient Portal on Influenza Vaccination Rates: a Randomized Clinical Trial

Abstract: Background Adult influenza vaccination rates are low. Tailored patient reminders might raise rates. Objective Evaluate impact of a health system’s patient portal reminders: (1) tailored to patient characteristics and (2) incorporating behavioral science strategies, on influenza vaccination rates among adults. Design Pragmatic 6-arm randomized trial across a health system during the 2019–2020 influenza vaccination se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…9 Future qualitative research should be done to ( 1 Past research on patient portal messages has largely examined its use among adult, non-Hispanic White, and privately insured populations. [18][19][20][21][22][23] In contrast, our study examined the use of patient portal messages among predominantly low-income non-Hispanic Black pediatric patients, a traditionally marginalized and harder to reach population. We conducted a separate trial with patients with an inactive EHR portal account to examine text and telephone reminder messages in that population, and rates of WCC completion were lower, ranging from 10% to 14%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Future qualitative research should be done to ( 1 Past research on patient portal messages has largely examined its use among adult, non-Hispanic White, and privately insured populations. [18][19][20][21][22][23] In contrast, our study examined the use of patient portal messages among predominantly low-income non-Hispanic Black pediatric patients, a traditionally marginalized and harder to reach population. We conducted a separate trial with patients with an inactive EHR portal account to examine text and telephone reminder messages in that population, and rates of WCC completion were lower, ranging from 10% to 14%.…”
Section: Discussionmentioning
confidence: 99%
“…Past research on patient portal messages has largely examined its use among adult, non-Hispanic White, and privately insured populations . In contrast, our study examined the use of patient portal messages among predominantly low-income non-Hispanic Black pediatric patients, a traditionally marginalized and harder to reach population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas another study using Epic MyChart patient portal messaging for late-season Influenza vaccination found no significant differences in vaccination uptake between the intervention and control groups [23]. Another recent study found no effect of tailored reminders (based on demographics with behavior economic messaging) sent by a health system's patient portal on influenza vaccination rates and a minimal effect (4.5%) among the young adult patient group who opened the pre-commitment portal messages asking if they planned to get vaccinated [34].…”
Section: Introductionmentioning
confidence: 97%
“…We created customized electronic reminder messages that pair strong provider recommendations with brief education and emphasis on the importance and cancer prevention, a recommended strategy for strengthening provider communication about HPV vaccination [18]. To our knowledge, this is the first study to include a patient's specific provider's name as part of the electronic patient reminder, rather than the organization's name [34].…”
Section: Introductionmentioning
confidence: 99%